Analisa Kadar Asam Urat pada Pasien Gagal Ginjal Kronik (GGK) di RSU Hidayah Deli Tua - Siti Suriani; Suharsih Suharsih; Febriantika Febriantika (Jurnal Anestesi, 2026)
Chronic kidney disease (CKD) is a condition characterized by a decline in kidney function, causing the kidneys to lose their ability to filter metabolic waste and maintain the balance of body fluids and electrolytes. One of the metabolic waste products that may increase in patients with CKD is uric acid, which is the final product of purine metabolism and is normally excreted through the kidneys. This study aimed to determine the uric acid levels in patients with chronic kidney disease at Hidayah General Hospital, Deli Tua. This research used a descriptive cross-sectional design. The sample consisted of 20 CKD patients who were hospitalized at Hidayah General Hospital, Deli Tua, during March–April 2023. The results showed that most patients experienced increased uric acid levels, including 13 female patients (60%) and 7 male patients (35%), while 1 female patient (5%) had normal uric acid levels. It can be concluded that the majority of chronic kidney disease patients had elevated uric acid levels, which is associated with impaired glomerular filtration so that the kidneys are unable to optimally excrete metabolic waste.